The Application of Logistics as Increase Income in Small Porte Company - Case Study in Salgados Mania - Azevedo Said, Victor; Barbosa de Alencar, David; Tregue Costa, Alexandra Priscilla; Alberto Oliveira de Freitas, Carlos (International Journal for Innovation Education and Research, 2019)
Logistics challenges are present in any organization, including small businesses. If today it is indispensable in large industries, for smaller companies the reality is different, since, in general, they do not have enough structures or employees to face adversity and meet their goals. Thus, it is becoming increasingly relevant to invest in tools that can bring improvements and results. Logistics encompasses activities that deal with the flow of material, human and information resources, but micro and small entrepreneurs generally do not handle all these stages of the process, which ends up making production work, often with lower efficiency than its total capacity, generating costs and making the company less productive. Lack of planning causes damage most of the time. This involves everything from inventory control to small processes that need human monitoring to happen. Due to the tools logistics offers to implement in any industry, regardless of size, opportunities for management improvement are growing, making the small business owner eligible to plan and think bigger about their business.